Pengaruh Harga dan Citra Merek Terhadap Keputusan Pembelian Dengan Minat Beli Sebagai Variabel Intervening (Studi Kasus Pemakai Sepatu Onitsuka Pada Mahasiswa FEB UMSU) - Romi Suhendra; Satria Mirsya Affandy Nasution (Fisarrearch, 2023)
This research is a study conducted for the effect of price and brand image on purchasing decisions with purchase intention as an intervening variable for the case study of the wearer of Onitsuka shoes in FEB UMSU students. This study uses a quantitative approach with primary data sources obtained from distributing questionnaires. The sampling technique in this study was using accidental sampling technique, with a total of 100 respondents. The analysis carried out in this study includes path analysis using the PLS application. The results showed that price has a positive and significant effect on Purchase Decisions on Consumers of Onitsuka Shoes at UMSU Students, Brand Image has a positive and significant effect on Purchase Decisions for Consumers of Onitsuka Shoes at UMSU Students, Price has a positive and significant effect on Buying Interests on Consumers Onitsuka Shoes at UMSU Students, Brand Image has a positive and significant effect on Buying Interest on Onitsuka Shoes consumers on UMSU Students, Purchase Intention has a positive and significant effect on Purchase Decisions on Onitsuka Shoes consumers on UMSU Students, Buying Intention is a link between the influence of Price on Purchase Decisions on Onitsuka Shoes consumers on UMSU Students and Buying Interest to be a link between the influence of Brand Image on Purchase Decisions for consumers of Onitsuka Shoes for UMSU Students